A Survey Study of Iranian Translation Students’ Use of Translation Language Learning Strategies and Related Beliefs - Asgarian, Amir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Translation language learning strategies, especially in relation to translation students, have not received adequate attention in the research to date. Therefore, the present study attempted to explore Iranian translation students‟ use of translation strategies, related beliefs and the effect of the factors of age, gender, university, academic achievement and self-rated proficiency on their beliefs and strategy use. It was a cross-sectional survey involving questionnaires and an interview. The survey was conducted with 320 undergraduate students majoring in English translation from six branches of Azad University in Iran. The results of the survey showed that the translation majors held mostly positive, somewhat conflicting beliefs though, about the role of translation in English language learning, that their repertoire and frequency of translation strategy use were not adequate yet, and, importantly that their university and academic achievement had an effect on their beliefs and strategy use. The study findings revealed that the translation students with strong positive beliefs about the role of translation in general and translation into their native language specifically tended to apply translation strategies for acquisition of English language skills with higher frequency. Moreover, the translation majors with favourable beliefs about the role of translation tended to report using translation strategies for acquisition of lexico-grammar in English frequently, and those with positive beliefs about reliance on their mother tongue would frequently make use of resource-related and social translation strategies. Further, the translation students from the North branches of Azad University held more positive beliefs about translation in English language learning and benefitted more from the use of translation strategies for acquisition of language skills in English than the translation majors in Tehran. Importantly, the translation students with higher achievement scores were more aware of L1 effects on their target language learning. In light of its findings, the present study offers pedagogical implications and makes suggestions for further research. Keywords: survey; beliefs; translation strategy; first language (L1); second language (L2)

Öz: Çeviri dil öğrenme stratejileri, özellikle mütercim tercümanlık öğrencileri bağlamında, yeterli derecede araştırılmamıştır. Zira bu kesitsel calışma, İranlı mütercim tercümanlık öğrencilerinin çeviri dil öğrenme stratejilerinin kullanımını, ilgili inançlarını ve yaş, cinsiyet, üniversite, akademik başarı ve yeterlik faktörlerin stratejilere ve inançlara etkisini incelemiştir. Çalışma, anket ve mülakat uygulamıştır. Araştırma, İran‟ın Azad Üniversitesi‟nin altı şubesinden 320 İngilizce mütercim tercümanlık ögrencileri ile yürütülmüştür. Analizler mütercim tercümanlık öğrencilerinin çevirinin İngiliz dili öğrenimindeki rolü ile ilgili genellikle olumlu, fakat bazen çelişkili inançlara sahip olduklarını göstermiştir. Ayrıyeten, öğrencilerin çeviri dil stratejilerinin repertuar ve kullanım sıklığı açısından çok yeterli olmadığını belirlemiştir. Ayrıca, bu bağlamda mütercim tercümanlık öğrencilerinin okudukları üniversite ve akademik başarılarının dil öğrenme stratejilerine ve ilgili inançlarına etkisi tespit edilmiştir. Çalışma bulguları, genellikle çeviri rolü ve özellikle kendi ana dillerine çeviri hususunda güçlü, olumlu inançları olan mütercim tercümanlık öğrencilerinin çok sıklıkla İngilizce dil becerilerinin edinimi için çeviri stratejilerini uygulamaya yöneldiğini ortaya çıkardı. Ayrıyeten, çeviri rolü hakkında olumlu inançları olan mütercim tercümanlık öğrencileri, İngilizce sözcük-dilbilgisi edinimleri için sık sık çeviri stratejileri kullandıklarını ve ana dillerine güven konusunda olumlu inançlara sahip olan bu kişiler, kaynakla ilgili stratejiler ve sosyal çeviri stratejilerinden sıklıkla faydanlandıklarını bildirdiler. Ayrıca, Azad Üniversitesi‟nin Kuzey şubelerindeki mütercim tercümanlık öğrencileri, Tahran'daki mütercim tercümanlık öğrencilerine nazaran İngilizce dil öğreniminde çeviri konusunda daha olumlu inançlar sergilemiş ve İngilizce dil becerilerinin edinimi için çeviri stratejilerinin kullanımından daha fazla yararlanmıştır. Daha da önemlisi, yüksek başarı puanlarına sahip olan mütercim tercümanlık öğrencileri, hedeflenen dil öğreniminde ana dilin etkilerinin daha çok farkındaydı. Bu bulguların ışığında, bu çalışma ileri araştırmalar ve dil eğitimi için önerilerde bulunmaktadır. Anahtar Kelimeler: Araştırma, inançlar, çeviri stratejisi, ana dil (L1), ikinci dil (L2)
Doctor of Philosophy in English Language Teaching (ELT). Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Assoc. Prof. Dr. Gülşen Musayeva Vefalı.
Keywords: English Language Teaching (ELT); English Language; Study and Teaching; Translation Language; Learning Strategies; Survey; beliefs; translation strategy; first language (L1); second language (L2)